Adsorption Refrigeration Characteristic of Attapulgite Based Calcium Chloride Composite Adsorbents - Wan Yi; Li Quanguo; Rui Zhengqiu; Cui Qun; Chen Haijun; Wang Haiyan; Yao Huqing (Zhileng xuebao)
The composite absorbent is mainly consisted of attapulgite and CaCl2 as the resources, which were prepared by the dissolution-mixed method, and the content of attapulgite in composite absorbent is 10%. Adsorption isotherms of ammonia on absorbents were determined by positive gravimetric method. Adsorption-desorption cycle performance and cooling characteristics of composite absorbent -ammonia working pairs was evaluated by self-made adsorption-desorption measuring device. Experimental results show that the equilibrium capacity of ammonia on the composite absorbent is up to 1.1kg/kg at 30℃, which is equal to that of CaCl2. The conditions of loading density 600kg/m3, adsorption temperature 30℃, ammonia evaporation pressure 0.25 MPa, desorption temperature 300℃, adsorption capacity of ammonia in the composite absorbent and its cyclic adsorption capacity is 0.89~0.92 kg/kg and 0.55~0.58 kg/kg, respectively, which is 1.7 times than that of CaCl2-ammonia working pairs. The cooling capacity is up to 761.84kJ/kg, which is increased by 70% compared to CaCl2/ ammonia. What’s more, composite absorbent has excellent adsorption and desorption stability.